Jurnalisme Bencana: Sebuah Tinjauan Etis - Muzayin Nazaruddin (Program Studi Ilmu Komunikasi, 2007)
Disaster journalism is how a mass media reports about disasters. As a new genre of journalism, disaster journalism hasn’t been studied more by academicians. Whereas, this new genre of journalism is very important, because Indonesia is susceptible country of disasters, mass media always reports about disasters enthusiastically, society entrust the information of disasters from mass media, and unclear information always happen in every disaster. In the fact, many weakness of disasters journalism in Indonesia, those are: mass media enthusiasm as a collector and distributor of disaster aids, more than their role to inform disasters clearly and completely, inconsistent news report, dramatisation tendency injoumalism report, and no role of early warning system of disasters in mass media. Start from these critics, this article proposes some principles in disaster journalism, such as: accuracy, humanism, commitment to rehabilitation, and control and advocacy. Besides that, this article suggests some agendas: comprehensive research about disaster journalism, code ethic of disaster journalism building, and disaster journalismtraining for Indonesian journalists.